Cultural and Socioeconomic Determinants of Mother’s Complementary Feeding Practices on Nutritional Status of Children Under Five: A Cross-Sectional Study in Lahore, Pakistan: Cultural and Socioeconomic Determinants of Mother’s Complementary Feeding Practices - Shahbaz, Misha; Saleem, Javeria; Hameed, Sajid; Javed, Farah; Sahar, Rameen; Khan, Ayesha; Jamshed, Samahir; Ijaz, Fiza (Pakistan Journal of Health Sciences, 2024)
Optimal nutrition and appropriate feeding practices in children determine the life and health of the child. Objectives: To investigate the cultural and socioeconomic determinants influencing mothers' complementary feeding practices, to evaluate mothers' knowledge, attitudes, and practices regarding complementary feeding, and to analyze the association between these factors and the nutritional status of children under 5. Methods: A cross-sectional study recruited 120 participants through a purposive sampling technique. Mothers with children under 5 were the targeted population living in Lahore. Data were collected through an online Google form and a self-administered, paper-based questionnaire divided into four sections: sociodemographic questions, questions on knowledge, attitude, and practices of complementary feeding, cultural practices, and questions related to the child's nutritional status. SPSS software version 27.0 was used for data analysis. Results: Almost (64.5%) of mothers knew that the correct age of initiation of complementary feeding was six months and were also aware of the risks of early initiation. The mother’s age (p-value=0.022) and literacy levels (p-value=0.010) were significant factors. Other factors included place of residence and age of initiation of complementary feeding (p-value=0.042), feeding environment (p-value<0.001), and responsive feeding practices (p-value<0.001). Conclusions: It was concluded that cultural beliefs and feeding practices that affect complementary feeding in Lahore were analyzed, with the results cementing the need for culturally responsive interventions and empowerment of mothers to mitigate malnutrition. The findings offer valuable insights contributing to the development of targeted interventions for similar communities.